Hedge fund vs. non-hedge fund institutional demand and the book-to-market effect - Caglayan, Mustafa Onur; Celiker, Umut; Sonaer, Gokhan (Journal of Banking & Finance, 2018)
Recent studies have documented that institutional investors trade contrary to the predictions of the book-to market anomaly. We examine whether a prominent sub-group of institutional investors, namely hedge funds, differ from other institutions in terms of their trading behavior with respect to the book-to-market effect. We find that hedge funds significantly alter their trading preferences with respect to growth and value stocks, after book-to-market values become public information. More importantly, we show that hedge funds are better able to identify overpriced growth stocks compared to other institutions. Our results contribute to the literature on institutional investors’ trading with respect to stock return anomalies.